Exposure of Women With and Without Disabilities to Violence and Discrimination: Evidence from Cross-sectional National Surveys in 29 Middle- and Low-Income Countries - Emerson, Eric (Journal of interpersonal violence, 2023)
There is a paucity of robust nationally representative data from low- and middle-income countries (LMICs) on the prevalence and risk factors associated with exposure of women with/without disability to either discrimination or violence. We undertook secondary analysis of data collected in Round 6 of UNICEF’s Multiple Indicator Cluster Surveys (MICS) involving nationally representative data from 29 countries with a total sample size of 320,426 women aged 18 to 49 years. We estimated: (1) prevalence rates for exposure to discrimination and violence among women with/without disabilities in the previous year in a range of LMICs; (2) the relative risk of exposure when adjusted for demographic and contextual characteristics; (3) the relative risk of exposure associated with specific functional difficulties associated with disabilities; and (4) the association between country-level estimates and national wealth and human development potential. Our results indicated that women with disabilities were approximately twice as likely as women without disabilities to be exposed to violence and discrimination in the past year, and approximately one-third more likely to feel unsafe in either their home or local neighbourhood and to be at greater risk of domestic violence. Risk of exposure was associated with national characteristics (national wealth, human development potential) and within country factors, especially relative household wealth and level of education. These results must be of concern on two counts. First, they attest to the ongoing violation of the human rights of women with disabilities. Second, they point to increased exposure among women with disabilities to several well-documented social determinants of poorer health.